Book Review: Archaeological and Anthropological Sciences by L. Shillito, E. Fairnell and H. S. Williams (eds) - Katy Whitaker (EXARC, 2014)
A set of eleven articles resulting from the call for papers for the Sixth UK Experimental Archaeology Conference (held in York in January 2012) is now published in a special issue of the Journal of Archaeological and Anthropological Sciences. Edited by the conference conveners, Lisa-Marie Shillito, Eva Fairnell and Helen S. Williams, the issue is available online (http://link.springer.com/journal/12520) prior to print publication anticipated later this year (2014).